Analisis Penyajian Konten Instagram Pada Akun @Shiftmedia.Id Sebagai Sarana Dakwah Digital - Hatta, Tengku Zaifach; Santoso, Puji (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
This study aims to analyze the presentation of Instagram content on the @shiftmedia.id account as a means of digital da'wah, with a focus on the visuals and audio used. In the digital era, social media such as Instagram has become an effective platform for conveying da'wah messages, especially to the younger generation. The @shiftmedia.id account was chosen because of its popularity and consistency in presenting relevant and interesting da'wah video content. The research method used is qualitative content analysis with a descriptive approach. The data collected includes da'wah video content uploaded by the @shiftmedia.id account. This study analyzes aspects such as text color, text message content, video background, and audio. The results of the study show that the @shiftmedia.id account has succeeded in utilizing the Instagram application as a means of presenting creative and easy-to-understand da'wah content. The content covers various religious topics presented to the younger generation and uses good language and is relevant to everyday life. In addition to the message content, the selection of appropriate text colors, and an interesting video background, audio that supports the audience's atmosphere is also an important element in presenting content. This study revealed that the @shiftmedia.id account has succeeded in optimizing Instagram as a means of digital da'wah. With the presentation of creative, effective, innovative, and relevant da'wah content, this account is able to reach a wide audience and make a positive contribution in spreading religious values in the digital era.